2018
DOI: 10.3389/fimmu.2018.01076
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal-Associated Invariant T Cells Are Depleted and Exhibit Altered Chemokine Receptor Expression and Elevated Granulocyte Macrophage-Colony Stimulating Factor Production During End-Stage Renal Disease

Abstract: BackgroundEnd-stage renal disease (ESRD) is associated with an increased susceptibility to infectious diseases, including infection with Mycobacterium tuberculosis (Mtb). Mucosal-associated invariant T (MAIT) cells recognize vitamin B metabolites produced by many bacterial species, including Mtb, and may play an important role in providing protective immunity against tuberculosis infection in the lung. To date, little is known about MAIT cell frequency, phenotype, or function in ESRD patients.MethodsMAIT cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…This is due to lowered sensitivity of the IGRA assay in detecting Mtb in ESRD groups which has been attributed to defective T cell function (272). γδ T cells in this co-infected population showed lowered expression of lung-homing receptors while MAIT cells were depleted in the periphery, with particular reductions in cells also associated with lung-trafficking (273,274). This indicates a potential role for unconventional T cells in controlling pulmonary TB infection.…”
Section: Antibodies and Immunity In Chronic Kidney Disease And Tubercmentioning
confidence: 94%
“…This is due to lowered sensitivity of the IGRA assay in detecting Mtb in ESRD groups which has been attributed to defective T cell function (272). γδ T cells in this co-infected population showed lowered expression of lung-homing receptors while MAIT cells were depleted in the periphery, with particular reductions in cells also associated with lung-trafficking (273,274). This indicates a potential role for unconventional T cells in controlling pulmonary TB infection.…”
Section: Antibodies and Immunity In Chronic Kidney Disease And Tubercmentioning
confidence: 94%
“…In circulation, the number of MAIT cells was not decreased pre‐ or 12‐months post‐transplantation. This is in contrast with studies that describe fewer circulating MAIT cells in patients on dialysis and also after transplantation compared to healthy controls [24, 25]. This may be explained by methodological differences, since, in one study [24], MAIT cells were not identified based on TCR specificity but by the expression of CD3, CD161, and TCR Vα7.2 chain, and, in the other study [25], only CD8 + circulating MAIT cells were analyzed.…”
Section: Discussionmentioning
confidence: 63%
“…This is in contrast with studies that describe fewer circulating MAIT cells in patients on dialysis and also after transplantation compared to healthy controls [24, 25]. This may be explained by methodological differences, since, in one study [24], MAIT cells were not identified based on TCR specificity but by the expression of CD3, CD161, and TCR Vα7.2 chain, and, in the other study [25], only CD8 + circulating MAIT cells were analyzed. In both the latter and the present study, the activation state of circulating MAIT cells, assessed by CD69 expression [25] was elevated, both pre‐ and post‐transplantation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations